RETRACTED: Perubahan fungsi kognitif dan psikomotor residen anestesiologi dan terapi intensif setelah 32 jam kerja - Muhammad Zulfadli Syahrul; Muhammad Ruswan Dachlan; Arif Hari Martono Marsaban; Diatri Nari Lastri (Majalah Kedokteran Andalas, 2017)
RETRACTEDFollowing a rigorous, carefully concerns and considered review of the article published in Majalah Kedokteran Andalas to article entitled "Perubahan fungsi kognitif dan psikomotor residen anestesiologi dan terapi intensif setelah 32 jam kerja" Vol 40, No 1, pp. 19-30, May 2017, DOI: http://dx.doi.org/10.22338/mka.v40.i1.p19-30.2017.This paper has been found to be in violation of the Majalah Kedokteran's Publication Ethics and has been retracted.The reason: Not all authors approve journal submission for publication based on the report from one of co-author.The document and its content has been removed from Majalah Kedokteran Andalas, and reasonable effort should be made to remove all references to this article.